Compliance of Scaffolder Workers in Using Full Body Harness through Rewards and Punishment as Intervening Variable - Siti Nurjannnah; Dadan Erwandi (Journal La Medihealtico, 2025)
The electronics manufacturing industry demands high levels of precision and accuracy, putting workers at risk of mental workload, which can impact work effectiveness and health. This study aims to analyze the level of mental workload among technicians in the electronics assembly maintenance division and identify the dominant factors influencing it. The study used a quantitative approach using the NASA-TLX instrument on 25 technicians, along with data uniformity and adequacy analysis to ensure the validity of the results. The results showed that technicians experienced high mental workload, with the highest score being 85.60 and the lowest being 68.50. The three main dimensions that contributed most were Mental Demand (average 312), Effort (278), and Physical Demand (250). The uniformity test yielded a BKA score of 90.12 and a BKB score of 66.30, indicating that the data met uniformity and adequacy requirements. These findings have practical implications for company management in designing ergonomic strategies and work policies to reduce mental workload. Recommendations include rotating technicians to reduce concentrated cognitive load, restructuring work hours and rest periods to optimize physical recovery, and scheduling maintenance shifts to reduce perceived performance pressure. This research contributes to scientific research by providing empirical evidence on mental workload in the electronics manufacturing industry and offering applicable work management strategies to improve technician well-being and productivity.